L’Ayurveda - Lucie Dejouhanet (EchoGéo, 2009)
Western societies are more and more interested in Eastern medicines. Among these ones, the Indian medicine Ayurveda is becoming significant. WHO encourages traditional medicine development in Southern countries, expecting an improvement in the health of populations forgotten by biomedical health systems. But the Ayurveda sector chose a more ambitious way for developing. Scientific validation methods and modernisation of its production made it a competitive medicine, challenging urban middle-class and foreign markets. Globalised Indian Ayurveda medicine sells « tradition » in order to conquer new markets.